Agreement between dribble and change of direction deficits to assess directional asymmetry in young elite football players - Trecroci, A.; Bongiovanni, T.; Cavaggioni, L.; Pasta, G.; Formenti, D.; Alberti, G. (symmetry, 2020)
This study aimed to examine the agreement between asymmetries of dribble and change of direction (COD) deficits and to determine their potential difference to each other. Sixteen young elite football players were recruited and tested for sprint (over 10 m), dribbling (90°CODdribbling) and COD (90°CODrunning) performance in dominant (fastest) and non-dominant (slowest) directions. Dribble and COD deficits were computed to express dribbling and COD ability without the influence of acceleration. The asymmetric index (AI%) of both dribble and COD deficits were obtained for both directions. The level of agreement between dribble and COD deficits was assessed by Cohen`s kappa statistic (k). Results showed that AI% measured by dribble and COD deficits presented a poor level of agreement (k = -0.159), indicating their imbalance did not favor the same direction. Moreover, AI% of the dribble deficit was significantly higher than those of the COD deficit. This study demonstrated that asymmetries in dribbling and change of direction performance (measured by dribble and COD deficit) were not in agreement to favor the same direction, also displaying a significant difference to each other. Practitioners should consider the task-specificity of asymmetry to reduce the imbalance in dribbling and COD performance.